Keragaan Industri Alas Kaki Kota Mojokerto Provinsi Jawa Timur - Maulana, Agus (Value : Journal of Management and Business, 2022)
The footwear industry in Mojokerto City has long been known as one of the producers of these products in East Java Province. Given that the industry deserves to be developed, the industry obtains the attention of the government. The study aims to discuss the performance of the footwear industry in Mojokerto City to support the industrial development effort. The method of analysis used descriptive methods based on qualitative research. The study results show that the industry contributes significantly to the economy of Mojokerto Municipality through a multiplier effect on the regional economy. It is indicated by the contribution of the industrial sub-sector based on Gross Regional Domestic Product and labor absorption. That condition is supported by industrial products that become regional prestige and have high local advantages/specifications.